Best Practices for Communicating about Outdoor Residential Water Conservation - Jacqueline Aenlle; Laura A. Sanagorski Warner (EDIS, 2020)
Extension communication efforts can be made more effective when following a strategic communication plan. To guide a strategic communication effort, it is imperative to have purposeful messaging along with an understanding of your target audience and communication channel. This document presents a synthesis of literature highlighting best communication practices in regard to water conservation efforts.